2015
DOI: 10.1073/pnas.1416330112
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pathways of RNA polymerase regulation by a phage-encoded factor

Abstract: Transcription antitermination is a common strategy of gene expression regulation, but only a few transcription antitermination factors have been studied in detail. Here, we dissect the transcription antitermination mechanism of Xanthomonas oryzae virus Xp10 protein p7, which binds host RNA polymerase (RNAP) and regulates both transcription initiation and termination. We show that p7 suppresses intrinsic termination by decreasing RNAP pausing and increasing the transcription complex stability, in cooperation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…NusA was previously shown to enhance pausing and intrinsic termination in various bacteria, including E. coli , Bacillus subtilis , T. thermophilus , and Xanthomonas oryzae . We demonstrated that Dra NusA also stimulates hairpin‐dependent pausing and intrinsic termination by Dra RNAP.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…NusA was previously shown to enhance pausing and intrinsic termination in various bacteria, including E. coli , Bacillus subtilis , T. thermophilus , and Xanthomonas oryzae . We demonstrated that Dra NusA also stimulates hairpin‐dependent pausing and intrinsic termination by Dra RNAP.…”
Section: Resultsmentioning
confidence: 56%
“…While the functions of some pauses are well established (synchronization of transcription with translation for hisP and, probably, consP), others may appear as an unavoidable consequence of variations in the transcribed DNA sequence. RNAP pausing is also the first step in the transcription termination pathway, and intrinsic terminators share common structural motifs with hairpin‐dependent pause signals, which may cause similar rearrangements of the TEC during termination .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, both Gfh1 and Gfh2 strongly enhance recognition of two common types of the pausing signals found in bacteria, consensus and hairpin-dependent pauses, by Dra RNAP. They also stimulate intrinsic termination, which likely proceeds through the same structural intermediate(s) as hairpin-dependent pausing (9,35,36). Previously, the pause RNA hairpin was shown to induce long-range conformational changes of the TEC, including opening of the clamp domain and inhibition of the TL folding (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…T7A1 promoter followed by λ tR2 terminator was obtained as in ( 20 ). DNA template containing a fragment of the E. coli rpoB gene fused to the λ P R promoter for measurements of elongation rates was described previously ( 21 ). DNA templates for analysis of hisP pausing were obtained by PCR from plasmid pIA226 containing λ P R promoter followed by the hisP site.…”
Section: Methodsmentioning
confidence: 99%